FAKTOR-FAKTOR YANG MEMPENGARUHI KESADARAN MASYARAKAT DALAM MEMBAYAR PAJAK KENDARAAN BERMOTOR (PKB) DI KOTA SURABAYA SELATAN - FITRI ANDARI, INDAH Fitri (Jurnal Akuntansi AKUNESA, 2014)
This study aimed to determine the factors that affect the public consciousness in a motor vehicle tax paid in Surabaya Selatan. Public awareness in paying taxes can affect the amount of tax revenue the area. Public awareness should be raised in order to pay the tax revenue target area can be achieved. The method used in this research is descriptive qualitative approach which is based on the data and information obtained through documents and interviews. The results showed that the factors that influence people's awareness in the motor vehicle tax paid in Surabaya Selatan include: a understanding of the taxpayer's tax purposes, services provided by the taxpayer to the tax man, the allocation of appropriate funds and targeted, public understanding of the sanctions that can be granted if the taxpayer does not undergo a tax payment, and adequate information about the way of taxation.   Keywords: Public Awareness,PKB